SCREENING OF INDONESIAN ORIGINAL BACTERIA VIBRIO SP AS A CAUSE OF SHRIMP DISEASES BASED ON 16S RIBOSOMAL DNA-TECHNIQUE - Feliatra Felix; Titania T Nugroho; Sila Silalahi; Yuslina Octavia (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2011)
Shrimp disease caused by Vibrio sp is one of the main limiting factors in the increasing production in shrimp farming. This disease may kill the shrimp and cause high loss in shrimp culture in South East and East Asia. Samples of 10 individuals of a ten months cultured giant tiger prawn as well as 1 liter pond water and sea waters were collected from shrimp pond in Bengkalis Island, Sumatra. Samples of shrimps were also collected from Jepara shrimp pond in Central Java and they were selected by looking at their behavior and unhealthy physical characteristics. Amplification, rDNA 16s sequencing and bioinformatics analysis to identify Vibrio species were conducted in Biotech Center, BPPT Serpong Banten. The results of DNA sequencing of each bacteria isolate were compared to DNA sequence from international DNA bank database. Tracing were made by BLAST (Basic Local Alignment Search Tool) system accessed through the internet at http://www./ncbi.nlm.nih.gov/blast. The result of this study found seven strains of Vibrio sp bacteria where five of which (V. alginolyticus, V. parahaemolyticus, V. harveyi, V. shilonii and V. vulnificus) were already registered in the world gen bank with homolog level above 97%. Meanwhile, another two strain found in this study were not found in the list of world gen bank and therefore are considered as native Vibrio sp bacteria from Indonesia.Keywords: Vibrio sp, bacteria, shrimp, aquaculture, fish disease